THE PRECAUTION OF THE GRAMMATICAL MEANING OF THE STUDENTS OF THE DAY SCHOOL FOR BOYS IN THE DEVELOPMENT OF LANGUAGE ABILITY - Dr. Dihya Uweed Harbi Al Arnoosy , Dr. Mohammed Abbas Mohammed (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
This study aims at identifying the linguistic ability of students in the fourth grade in preparatory schools when reading. The researcher tried to limit some of these linguistic abilities and determine their types of reading. The Arabic language is the mirror of the schools in the linguistic aspect. To achieve the goal of the research, the researcher chose several schools in the province of Babylon, the Hashemite and revealed the weakness of their language ability to read the Arabic language and then concluded the researchers with several recommendations and some suggestions.